Economic Burden of Paroxysmal Nocturnal Hemoglobinuria (PNH) and Secondary Problems Caused by PNH - Sina Dadfar; Meysam Seyedifar; Sahar Roozbahani; Fatemeh Soleymani (Tehran University of Medical Sciences, 2022)
Background: Paroxysmal Nocturnal Hemoglobinuria (PNH) is a rare, acquired disorder of hematopoietic stem cells, in which red blood cells become susceptible to complement-mediated hemolysis. PNH is associated with a wide range of medical consequences and costs. This study was done to estimate the economic burden of PNH and the secondary consequences caused by PNH in Iran. Methods: This study is a cross-sectional and non-interventional study conducted using the cost-of-illness framework. The top-down prevalence method was used to quantify the annual PNH-related costs. This study was conducted from the societal perspective, including all direct medical, non-medical, and indirect costs associated with PNH. Productivity losses were calculated using the human capital method. Costs were collected using the relative value unit of health services in Iran, related literature, and from one of the referral hospitals in Iran, as well. Results: The average annual costs of blood transfusion and anemia, thromboembolic events, and renal problems are estimated to be around $5400, $5382, and $6422, respectively. The total average costs of the three mentioned consequences caused by PNH are estimated to be $17,204 US dollars per PNH patient per year in Iran. Conclusion: This study suggests that the average cost of managing anemia, blood transfusion, thromboembolic events, and renal problems in PNH equals $17,204 annually. Dependent on the severity of the disease and other factors, this amount could increase significantly. Additional cost-effectiveness studies should be carried out to identify the most cost-efficient disease management protocol.